DESIGN OF CULTURAL AND CREATIVE PRODUCTS IN ANKANG REGION FROM THE PERSPECTIVE OF REGIONAL CULTURE - QIANG, W.; PASHKEVYCH, K. L. (Art and Design, 2023)
The purpose of this study is to develop design for cultural and creative products based on the regional culture of each district and county in Ankang City, Shaanxi Province, China. This study utilizes an interdisciplinary research method. The theory of translation in linguistics and the three-layer structure of cultural attributes are integrated into the design of regional cultural and creative products, and the material, spiritual, and behavioral elements of local culture are translated into the form, semantics, and function of cultural and creative products, respectively. By using this method, various local cultural elements are mined and integrated into product design to increase the sense of cultural identity. Based on the research status of regional material or immaterial culture and the current situation of local development in Ankang, Shaanxi Province, we explore the practical significance and value of integrating regional cultural elements into cultural and creative products, introduce design translation theory and cultural triple structure, use the local cultural characteristics of Ankang to enhance the added value of cultural and creative products, strengthen the cultural identity of tourists, and help the heritage and development of Ankang regional culture in the era. In this study, we adopt the transliteration theory to analyze the regional cultural elements from multiple perspectives and present them through visual forms. It has been proved that the translation theory can highlight the regional characteristics of cultural and creative product design from multiple dimensions. Transcreation theory combined with cultural triple architecture can be used in the development of cultural and creative products in other regions, thus establishing a more complete regional culture discovery and presentation as an important tool. Second, by developing cultural and creative products in the Ankang region, the local city image can be established and the development of related tourism industries can be promoted.